Evaluating the Role of Breathing Guidance on Game-Based Interventions for Relaxation Training - Gummidela, Venkata Nitin Chakravarthy; Silva, Dennis R. da Cunha; Gutierrez-Osuna, Ricardo (Frontiers in Digital Health, 2021)
Working in a fast-paced environment can lead to shallow breathing, which can exacerbate stress and anxiety. To address this issue, this study aimed to develop micro-interventions that can promote deep breathing in the presence of stressors. First, we examined two types of guides to help individuals learn deep breathing: biofeedback and a pacing signal. Second, we examined whether these two breathing guides can be integrated into a casual game, to increase enjoyment and skill transfer. We used a 2x2 factorial design, with breathing guide (biofeedback vs. pacing) and gaming (game vs. no game) as independent factors. This led to four experimental groups: biofeedback alone, biofeedback with game, pacing alone, and pacing with game. In a first experiment, we evaluated the treatments in a laboratory setting, where 30 healthy participants completed a stressful task before and after performing one of the treatments (or a control condition). Two-way ANOVA of breathing rates, with treatment and time (pre-test, post-test) as independent factors shows a significant effect for time (F(4,50)=18.49,p<0.001) and treatment (F(4,50)=2.54,p=0.05), but no interaction effects. Post-hoc t-tests between pre and post-test breathing rates shows statistical significance for the game with biofeedback group (t(5)=5.94,p=0.001), but not for the other four groups, indicating that only game with biofeedback led to skill transfer at post-test. Further, two-way ANOVA of self-reported enjoyment scores, with breathing guide and game as independent factors, found a main effect for game (t(34)=1.99,p<0.001), indicating that the game interventions were more enjoyable than the non-game interventions. In a second experiment, conducted ambulatorily, 36 healthy participants practiced their assigned treatment as they saw fit during the day. We found that the game interventions were practiced more often than the non-game interventions (t(34)=1.99,p=0.027). However, we also found that participants in the game interventions could only achieve deep breathing 50% of the times, whereas participants in the non-game groups succeeded 85% of the times, which indicated that the former need adequate training time to be effective. Finally, participant feedback indicated that the non-game interventions were better at promoting in-the-moment relaxation, whereas the game-based interventions were more successful at promoting deep breathing during stressful tasks.